Fahrerassistenzsysteme zur energieeffizienten Längsregelung - Analyse und Optimierung der Fahrsicherheit - Hülsebusch, Dirk (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2018)
The most important drivers of driver assistance systems are improving driving safety and energy efficiency. In many cases, energy-efficient driving also implies a safe driving technique. In some cases, however, energy-efficient driving can lead to a decline in driving safety. This work therefore investigates whether an energy-efficient driving style by the forward vehicle leads to a decline in driving safety.